The role of dynamic angionephroscintigraphy in the diagnosis of urinary tract incompetence after kidney transplantation - A. V. Pinchuk; N. V. Shmarina; E. V. Migunova; A. Rustambek Uulu; N. E. Kudryashova; I. V. Dmitriev; D. V. Lonshakov; A. G. Balkarov (Трансплантология (Москва))
Introduction. The urinary tract incompetence ("extravasation of urine") of the renal allograft is the most common urological complication in the early postoperative period.The purpose was to evaluate the efficacy of the dynamic angionephroscintigraphy technique in diagnosing the extravasation of urine after kidney transplantation.Material and methods. The results of dynamic angionephroscintigraphy were analyzed for the purpose of verifying/ diagnosing the extravasation of urine in 63 patients who underwent kidney transplantation at N.V. Sklifosovsky Research Institute for Emergency Medicine in 2019. Dynamic angionephroscintigraphy of the renal allograft was performed with the glomerulotropic 99mTc-pentatech radiopharmaceutical on a two-detector single-photon emission tomography "Infinia II" and a combined CT SPECT / CT system "Discovery NM/CT670".Results. The sensitivity of dynamic angionephroscintigraphy in detecting the extravasation of urine was 100%, the specificity was 88%, and the accuracy of the method was 89%.Conclusion. Dynamic angionephroscintigraphy is a highly sensitive and specific method for diagnosing the extravasation of urine after kidney transplantation.